Mesenchymal Stem Cell Therapy for Aging Frailty - Schulman, Ivonne Hernandez; Balkan, Wayne; Hare, Joshua M. (Frontiers in Nutrition, 2018)
Chronic diseases and degenerative conditions are strongly linked with the geriatric syndrome of frailty and account for a disproportionate percentage of the health care budget. Frailty increases the risk of falls, hospitalization, institutionalization, disability, and death. By definition, frailty syndrome is characterized by declines in lean body mass, strength, endurance, balance, gait speed, activity and energy levels, and organ physiologic reserve. Collectively, these changes lead to the loss of homeostasis and capability to withstand stressors and resulting vulnerabilities. There is a strong link between frailty, inflammation, and the impaired ability to repair tissue injury due to decreases in endogenous stem cell production. Although exercise and nutritional supplementation provide benefit to frail patients, there are currently no specific therapies for frailty. Bone marrow-derived allogeneic mesenchymal stem cells (MSCs) provide therapeutic benefits in heart failure patients irrespective of age. MSCs contribute to cellular repair and tissue regeneration through their multilineage differentiation capacity, immunomodulatory and anti-inflammatory effects, homing and migratory capacity to injury sites, and stimulatory effect on endogenous tissue progenitors. The advantages of using MSCs as a therapeutic strategy include standardization of isolation and culture expansion techniques and safety in allogeneic transplantation. Based on this evidence, we performed a randomized, double-blinded, dose-finding study in elderly, frail individuals and showed that intravenously delivered allogeneic MSCs are safe and produce significant improvements in physical performance measures and inflammatory biomarkers. We thus propose that frailty can be treated and the link between frailty and chronic inflammation offers a potential therapeutic target, addressable by cell therapy.